2016
DOI: 10.1016/j.bpj.2015.11.1073
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Nucleotide-Dependent Structural Transitions in the Kinesin-1 Hydrolysis Cycle

Abstract: To dissect the kinetics of structural transitions underlying the stepping cycle of kinesin-1 at physiological ATP, we used interferometric scattering microscopy to track the position of gold nanoparticles attached to individual motor domains in processively stepping dimers. The high spatiotemporal resolution of this method enabled real-time recording of structural changes in the protein as it walked at~100 steps per second. Labeled heads resided stably at positions 16.4 nm apart, corresponding to a microtubule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 0 publications
4
40
0
Order By: Relevance
“…In kinesin-5, which has a unique L5 latch 45 , the coupling between the switch and neck linker domains is diminished and the structural transition are not as sharp as kinesin-1 17,46 . These differences may lead to the slower observed MT-stimulated ADP release in Eg5 compared to kinesin-1 13,14,39 . One possible inhibition mechanism is that in apo-Eg5, binding of rigor inhibitors to the α4/α6 interface may allosterically close the nucleotide cleft, thereby blocking nucleotide exchange 33,35 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In kinesin-5, which has a unique L5 latch 45 , the coupling between the switch and neck linker domains is diminished and the structural transition are not as sharp as kinesin-1 17,46 . These differences may lead to the slower observed MT-stimulated ADP release in Eg5 compared to kinesin-1 13,14,39 . One possible inhibition mechanism is that in apo-Eg5, binding of rigor inhibitors to the α4/α6 interface may allosterically close the nucleotide cleft, thereby blocking nucleotide exchange 33,35 .…”
Section: Resultsmentioning
confidence: 99%
“…Engineered Eg5 dimers have a large stall force, and display minimal processivity 11 , consistent with Eg5 working in teams during spindle formation 2,12 . Additionally, Eg5 walks with a 10-fold slower velocity than kinesin-1 11,13,14 , and it is able to resist large mechanical loads (~10 pN) in either the plus- or minus-end directions 1517 , which contrasts with the directional dependence of kinesin-1 18 . These properties likely result, at least in part, from the motor spending most of its ATP hydrolysis cycle in a state in which both heads are bound to the microtubule (two-head-bound state), a property not shared by kinesin-1 11,14 .…”
mentioning
confidence: 99%
“…33 Kinesin walks by alternating stepping of its two motor domain heads in a hand-over-hand (HoH) motility. 2 The stepping movement of a single head of a kinesin dimer has been studied extensively by labeling with SA-coated QDs 4 or gold nanoparticles, 34 although these large (>20 nm diameter) probes may interfere with kinesin motility. We reasoned that our compact BG-coated QDs enable higher labeling efficiency with minimal perturbation to kinesin motility.…”
Section: Resultsmentioning
confidence: 99%
“…The step analysis revealed that a kinesin head takes 16 nm steps at limited ATP concentration, in agreement with previous studies and demonstrating that labeling with these QDs does not measurably alter kinesin motions. 2, 34 …”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, ADP is released from this new leading head resulting in both heads bound to the microtubule (Fig. 1, E4 and E5) (27).…”
mentioning
confidence: 99%